Los marcadores verbales de modalidad epistémica y su papel en el desarrollo de las competencias comunicativas - Pihler Ciglič, Barbara (Linguistica (Ljubljana), 2014)
Modality in language, one of the characteristic phenomena of the process of communication, has to do with, in the broad sense, the mindset that the speaker indicates in his words while describing, questioning, or wanting to draw attention to what he is saying. Traditionally there is a tendency to gather, under the broad label of linguistic modality, a variety of different forms: verbal mode, auxiliary verbs, certain adverbs and particles, intonation, etc. The aim of this study is to analyze the Spanish verbal markers and their possibilities to express epistemic modality, which is defined as the linguistic expression of the degree of commitment that the speaker assumes about the factuality of his statement (Lyons 1977, Palmer 1986). The study focuses, first, on modal verbal periphrases and some of the tenses which can indicate the epistemic modality and/or evidentiality in certain contexts through the so-called "quotative" or "polyphonic" uses. The second part of this study consists of an analysis of the systematization of these resources in six selected manuals of Spanish as a Second Language (SSL; levels B1, B2 and C1 according to CEFR), with special attention to its contribution to the development of communicative competences (linguistic, sociolinguistic and pragmatic competence, again according to CEFR). We believe that the explicit study of epistemic modality in the SSL classroom effectively contributes to a good command of Spanish, and therefore deserves more attention.
Keywords: Cadre européen commun de référence pour les langues; CECRL; epistemična modalnost; espagnol; glagolski kazalniki; marqueurs verbaux; modalité épistémique; SEJO; Skupni evropski jezikovni okvir; Spanish; sporazumevalne jezikovne zmožnosti; sporazumevalne zmožnosti; španščina; tuji jeziki